2013
DOI: 10.1016/j.biortech.2013.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-based component profiling of Halomonas sp. KM-1 during different growth phases in poly(3-hydroxybutyrate) production

Abstract: To investigate the relationship between the production of poly(3-hydroxybutyrate) (PHB) and metabolic changes during different growth phases, a non-sterile batch fermentation process involving an alkalophilic and halophilic bacterium, Halomonas sp. KM-1, was used. Intracellular metabolites were analyzed using gas chromatography-mass spectrometry to characterize the metabolic profile. Significant changes relating to PHB production were observed in the TCA cycle, lipid-synthesis and amino acid biosynthetic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…35,36 For each strain, our results showed that most of the changes between the growth phases correspond to the upregulation of a large part of the metabolites during the stationary phase. This trend was already observed in previous studies, 31,32 but opposite results have also been described due to distinct metabolome coverage or studied microorganism. 13 These bibliographic data were also in accordance with the different behavior of each of the four strains when the metabolome, restricted to the extraction and analytical procedures, was investigated at different time points of the growth curve.…”
Section: Impact Of the Growth Phase (Experiments #3)supporting
confidence: 73%
“…35,36 For each strain, our results showed that most of the changes between the growth phases correspond to the upregulation of a large part of the metabolites during the stationary phase. This trend was already observed in previous studies, 31,32 but opposite results have also been described due to distinct metabolome coverage or studied microorganism. 13 These bibliographic data were also in accordance with the different behavior of each of the four strains when the metabolome, restricted to the extraction and analytical procedures, was investigated at different time points of the growth curve.…”
Section: Impact Of the Growth Phase (Experiments #3)supporting
confidence: 73%
“…workers reported that along with PHA production other products like glycerol and different amino acids viz., serine, glycine and glutamine might also be generated when glucose is used as a substrate (Jin et al, 2013). Hence the unknown organic matter (0.37 g/l) may contribute to byproducts such as glycerol and amino acids.…”
Section: Bioplastics Production Under Different Microenvironmentmentioning
confidence: 98%
“…The metabolic profiling of Halomonas sp. during different growth phases characterized the metabolites regulation pattern, which is beneficial to optimize the production of poly(3-hydroxybutyrate) (Jin et al, 2013). Similar study of Saccharomyces cerevisiae during different growth stages revealed that the oscillation of metabolites abundance contributed to controlling the temporal regulation of cellular processes (Tu et al, 2007).…”
Section: Introductionmentioning
confidence: 89%